2008
DOI: 10.1136/bjsm.2008.052522
|View full text |Cite
|
Sign up to set email alerts
|

Gait mechanics after ACL reconstruction: implications for the early onset of knee osteoarthritis

Abstract: It seems that individuals who have undergone ACL reconstruction exhibit an increased peak knee-abduction moment that may establish a potential mechanism of the earlier onset of knee OA in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
139
6
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 33 publications
7
139
6
1
Order By: Relevance
“…Previously, ACLinjured individuals were known to be at high risk for ACL injury [19][20][21] and to have faulty movement patterns. [22][23][24] Removing these athletes may have further limited the predictive ability of the LESS in this population because many individuals who could have been detected by the LESS might have been filtered from the source population. Another factor to consider when comparing our observations and those of Smith et al 15 is differences in sport or athlete type between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, ACLinjured individuals were known to be at high risk for ACL injury [19][20][21] and to have faulty movement patterns. [22][23][24] Removing these athletes may have further limited the predictive ability of the LESS in this population because many individuals who could have been detected by the LESS might have been filtered from the source population. Another factor to consider when comparing our observations and those of Smith et al 15 is differences in sport or athlete type between studies.…”
Section: Discussionmentioning
confidence: 99%
“…The lasting effects of ACLR on an individual's knee biomechanics, as well as their muscle activation patterns, morphologies and strengths, may influence subsequent knee OA risk. During walking, ACLR individuals have a smaller knee flexion angle and moment (39), an increased knee adduction moment (9), and reduced vasti activation (6). Moreover, the donor muscles from which the ACL autograft is harvested subsequently experience fatty infiltration (40), atrophy (8,40) and muscle-belly retraction (50).…”
Section: Introductionmentioning
confidence: 99%
“…Although researchers 12,13 have demonstrated that greater medial compartment loading occurs during walking after ACL reconstruction, on the basis of our results, it does not appear that lateral BBs sustained concurrently with ACL injury contribute to these altered frontal-plane biomechanics. However, in these previous studies, the KAMs were substantially larger than those we reported, and the participants were tested postoperatively.…”
Section: Discussionmentioning
confidence: 75%
“…However, in these previous studies, the KAMs were substantially larger than those we reported, and the participants were tested postoperatively. In fact, Butler et al 12 tested participants an average of 5 years postoperatively, a time when radiographic osteoarthritis may be influencing lower extremity biomechanics. [24][25][26] When comparing KAM in the ACL þ BB and control groups with the ACL-injury group, we observed strong effect sizes with CIs that did not cross zero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation